A Copper(I) Complex with Two Unpaired Electrons, Synthesised by Oxidation of a Copper(II) Complex with Two Redox‐Active Ligands. Issue 43 (17th September 2021) - Werr, Marco; Kaifer, Elisabeth; Enders, Markus; Asyuda, Andika; Zharnikov, Michael; Himmel, Hans‐Jörg
Abstract: Two homoleptic copper(II) complexes [Cu(L1)2 ] and [Cu(L2)2 ] with anionic redox‐active ligands were synthesised, one with urea azine (L1) and the other with thio‐urea azine (L2) ligands. One‐electron oxidation of the complexes initiates an unprecedented redox‐induced electron transfer process, leading to monocationic copper(I) complexes [Cu(L1)2 ] + and [Cu(L2)2 ] + with two oxidised ligands. While [Cu(L1)2 ] + is best described as a Cu I complex with two neutral radical ligands that couple antiferromagnetically, [Cu(L2)2 ] + is a Cu I complex with two clearly different ligand units in the solid state and with a magnetic susceptibility close to a diamagnetic compound. Further one‐electron oxidation of the complex with L1 ligands results in a dication [Cu(L1)2 ] 2+, best described as a Cu I complex with a twofold oxidised, monocationic ligand and a neutral radical ligand. The stability in at least three redox states, the accumulation of spin density at the ligands and the facile ligand‐metal electron transfer make these complexes highly attractive for a variety of applications; here the catalytic aerobic oxidation of alcohols to aldehydes is tested. Abstract : Oxidation‐induced reduction: The oxidation of mononuclear Cu II complexes with novel unsymmetric redox‐active urea azine or thio‐urea azine ligands leads to metal reduction and formation of complexes with intriguing electronic structures. The stability in several redox states is the basis for their first application in catalytic aerobic alcohol oxidation.